(untitled) (Nigerian Journal of Technology, 2022)
Monthly production rates of most surface mines fluctuate with season and the Nzema Gold Mine is no exception. Located in the western region of Ghana, which is considered the wettest part of the country, the monthly production rates of the mine fluctuate with rainfall. Data covering three years were obtained from the mine and subjected to some statistical analyses including regression analysis and t-test. Using regression analysis, the production data were regressed on the rainfall records to establish a coefficient of determination (R2) and also to observe the general trend between the two variables. The obtained coefficient of determination was further scrutinized with a t-test to prove the existence of a linear correlation between rainfall and production. The results obtained show that there is no linear correlation between rainfall and production in the Nzema Gold Mine. Nevertheless, the presence of rainfall in the mine has an impact on production values, preventing the mine from meeting its desired production targets. From the results, rainfall comes third place on the hierarchy of general delays with a percentage contribution of 13% and causes an average loss of about 4,145 Bank Cubic Metre (BCM) worth of material annually. The presence of rainfall also introduces some benefits as well as deprivations to the mine, causing an average of about 243,000 worth of fuel to be saved concerning the water dust suppression activities, and an average of about 273,000 worth of fuel to be lost on dewatering pumps.